The Contribution of Genetic Variation and Aberrant Methylation of Aryl Hydrocarbon Receptor Signaling Pathway Genes to Rheumatoid Arthritis - Zhang, Tian-Ping; Li, Rui; Li, Hong-Miao; Xiang, Nan; Tan, Zhen; Wang, Guo-Sheng; Li, Xiao-Mei (Frontiers in Immunology, 2022)
The aryl hydrocarbon receptor (AHR) signaling pathway participates in immune regulation of multiple autoimmune diseases, including rheumatoid arthritis (RA). We conducted this study to investigate the association of AHR signaling pathway genes (AHR, ARNT, AHRR) single nucleotide polymorphisms (SNPs), as well as their methylation levels, with RA susceptibility. Nine SNPs (AHR gene rs2066853, rs2158041, rs2282885, ARNT gene rs10847, rs1889740, rs11204735, AHRR gene rs2292596, rs2672725, rs349583) were genotyped via improved multiple ligase detection reaction (iMLDR) in 479 RA patients and 496 healthy controls. We used the Illumina Hiseq platform to detect methylation levels of these genes in 122 RA patients and 123 healthy controls. A significant increase in rs11204735 C allele frequency was observed in RA patients when compared to controls. Further, rs11204735 polymorphism was associated with a decreased risk of RA under the dominant model. ARNT CCC haplotype frequency was significantly increased in RA patients in comparison to controls. In the AHRR gene, rs2672725 GG genotype, G allele frequencies were significantly related to an increased risk of RA and rs2292596, rs2672725 polymorphism were significantly associated with an increased risk of RA under the dominant model, recessive model, respectively. However, no significant association was identified between AHR gene polymorphism and RA susceptibility. The AHR methylation level in RA patients was significantly higher than the controls, while AHRR methylation level was abnormally reduced in RA patients. In addition, AHRR rs2672725 genotype distribution was significantly associated with the AHRR methylation level among RA patients. In summary, ARNT rs11204735, AHRR rs2292596, and rs2672725 polymorphisms were associated with RA susceptibility and altered AHR, AHRR methylation levels were related to the risk of RA.